A Viable Strategy for Improving Crop Productivity under Sustainable Agriculture - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Crop breeding programmes so far have concentrated more on developing high yielding varieties of major food crops under optimal input or high input conditions. Thanks to the breeders for producing high yielding crop cultivars under high input situations, we are able to feed billions of hungry people and provide clothing.However, little progress has been made in the past fifty years to develop genotypes capable of producing good harvest under low input and adverse agricultural conditions. Essentially, the best varieties that give good yield under high input condition often fail miserably under low input conditions. It needs to be mentioned here that 1/5thof the arable land of the world is arid and semi-arid and 2/3rdof it is saline thereby affecting crop productivity severely…….